Meiotic pairing of sex chromosome fragments and its relation to atypical transmission of a sex-linked marker in Ephestia kuehniella (Insecta: Lepidoptera) - Marec, F; Tothova, A; Sahara, K; Traut, W (Heredity, 2001)
The physical basis of non-Mendelian segregation of a sex-linked marker was studied in sex- chromosome mutant females of eight ASF ('abnormal segregating females') lines in the flour moth, Ephestia kuehniella. Electron microscopical analysis of microspread synaptonemal complexes revealed that in one line, the Z chromosome segment that contained the dz+ allele was translocated onto an autosome. The resulting quadrivalent visible in early female meiosis was 'corrected' into two bivalents in later stages. This explains autosomal inheritance of the sex chromosome marker in this strain. In the other seven ASF lines, the type of meiotic pairing of an additional fragment (Zdz+) of the Z chromosome was responsible for abnormal segregation of the marker gene. In several of these lines, Zdz+ contained a piece of the W chromosome in addition to the Z segment, as was confirmed by comparative genomic hybridization (CGH). Zdz+ formed three alternative pairing configurations with the original sex chromosomes: (i) a WZZdz+ trivalent, (ii) a WZ bivalent and a Zdz+ univalent or (iii) a ZZdz+ bivalent and a W univalent. In the most frequent WZZdz+ configuration, Zdz+ synapsed with Z and, consequently, segregated with W, simulating W linkage. This explains the predominant occurrence of the parental phenotypes in the progeny. Zdz+ univalents or W univalents, on the other hand, segregated randomly, resulting in both parental and nonparental phenotypes. In two of these lines, the Zdz+ was transmitted only to females. The results suggest that the W chromosome segment in Zdz+ of these lines contains a male-killing factor which makes it incompatible with male development. Our data provide direct evidence for the regular transmission of radiation-induced fragments from lepidopteran chromosomes through more than 50 generations. This is facilitated by the holokinetic nature of lepidopteran chromosomes. We conclude that Zdz+ fragments may persist as long as they possess active kinetochore elements.
Keywords: Chromosome Pairing; genetické markery; Moths; synaptonemální komplex; párování chromozomů; Female; meióza; Animals; ženské pohlaví; mužské pohlaví; Male; Meiosis; Sex Chromosomes; zvířata; pohlavní chromozomy; Synaptonemal Complex; můry; Genetic Markers